The Influence of Qris-Based Sharia Fintech Payments on Financial Management Behavior With Financial Literacy as an Intervening Variable (Syarikat: Jurnal Rumpun Ekonomi Syariah, 2025)
This study aims to examine the influence of QRIS-based Sharia fintech payments on financial management behavior, with financial literacy serving as an intervening variable. The research also takes into account the growth of Sharia fintech, which operates in accordance with Islamic principles such as fairness, transparency, and the prohibition of riba (usury), gharar (uncertainty), and maysir (gambling). Sharia fintech offers various services, including Sharia-compliant payments, halal investments, Islamic crowdfunding, and inclusive microfinancing. With rising public awareness of the importance of Sharia-compliant financial products, this form of fintech has emerged as a relevant alternative in promoting financial inclusion. The study population consists of students from the Faculty of Economics and Business at the State University of Malang who use QRIS-based Sharia digital payment systems. The sample was selected through purposive sampling based on relevant criteria. The sample size was determined using Roscoe’s guideline, ranging between 30 and 500 respondents, with a final sample of 100 participants. Data analysis was conducted using the Partial Least Squares (PLS) method via SmartPLS version 3.29, involving both the measurement model (outer model) and the structural model (inner model). The results reveal that Sharia fintech payments do not have a direct effect on financial management behavior. However, an indirect effect exists through financial literacy. These findings underscore the crucial role of financial literacy in enhancing the effectiveness of Sharia fintech services, which have the potential to meet the financial needs of society in a manner that aligns with Islamic values. This study is subject to several limitations. The sample is limited to students from a single institution, which may restrict the generalizability of the findings. Furthermore, the use of a purely quantitative approach limits the ability to explore in-depth insights into users’ perceptions and motivations in adopting Sharia fintech services. Future research is encouraged to broaden the demographic and institutional scope and to incorporate mixed-method approaches to gain a more comprehensive understanding.